Preparation method and application of methylated aminocaprolactam and cleaning / sterilizing material
By methylating aminocaprolactam with methanol in the presence of a catalyst, avoiding the use of toxic reagents, and using two-component supported catalysts, the safety and environmental pollution problems of the preparation method of methylated aminocaprolactam in the prior art are solved. It achieves high selectivity and green environmental protection synthesis, suitable for the production of cleaning/sterilization materials.
Patent Information
- Application Number
- CN202310701799.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-06-13
AI Technical Summary
The existing preparation methods for methylated aminocaprolactam use toxic formaldehyde and halogenated alkylating reagents, resulting in low selectivity, harsh process conditions, low safety and environmental pollution, and high equipment design and safety requirements.
In the presence of a catalyst, the aminocaprolactam is methylated with methanol to avoid the use of aldehydes and halogenates. A two-component supported catalyst is used to exist in the form of an alloy to regulate the structure and content of the support and active components to achieve the target product Selectivity can be regulated and green and safe synthesis.
It realizes highly selective, green and environmentally friendly methylated aminocapollactam preparation, simplifies the process flow, reduces operating risks and environmental pollution, facilitates industrial production, and is used to prepare cleaning/sterilization materials.
Smart Images

Figure CN119118919A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic synthesis, and in particular to a preparation method of methylated aminocaprolactam, an application of the methylated aminocaprolactam prepared by the preparation method, and a cleaning / sterilization material containing the methylated aminocaprolactam. Background Art
[0002] With the development of economy, people pay more and more attention to their quality of life and safety and health, and put forward higher requirements for the hygiene of the items used for food, clothing, housing and transportation. However, the spread of bacteria and viruses continues to threaten human life and health, which makes the research and development and promotion of antibacterial materials of great significance. In recent years, polymer materials with self-cleaning / antibacterial functions have become an important growth point for scientific research and industrialization due to their intrinsic antibacterial properties and good mechanical properties. The synthesis of antibacterial monomers is a key link in the research and development and promotion of such self-cleaning / antibacterial materials. Among them, aminocaprolactam and its α-amino derivatives are a class of antibacterial monomers with great research value and development potential.
[0003] CN111116472A discloses a method for preparing an aminocaprolactam derivative monomer; CN104629045A discloses a method for preparing ε-polylysine by ring-opening polymerization, including the protection / deprotection process of the α-amino group of aminocaprolactam; CN104387323A discloses a method for preparing an aminocaprolactam compound having a halogenated toluene derivative as an α-amino substituent; CN103694174A discloses a method for preparing an aminocaprolactam compound having a benzaldehyde derivative as an α-amino substituent. The above-mentioned methods for preparing the derivatized aminocaprolactam monomer all have the following problems: (1) the α-amino derivatization reagent is formaldehyde, bromide, etc. These derivatization reagents are highly toxic, have poor chemical stability, and cause serious pollution to the environment; (2) when formaldehyde is used as an alkylating agent, a hydrogenation reagent needs to be introduced into the reaction system, and the hydrogenation reagent puts forward high requirements on the design and safety of the reaction device, and has the problems of high cost, low safety, and environmental pollution.
[0004] Therefore, there is an urgent need to develop an efficient and environmentally friendly method for preparing methylated aminocaprolactam. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of the existing preparation method of methylated aminoamide, such as the use of alkylating agents such as formaldehyde and halogenated compounds and hydrogenating agents, resulting in low selectivity of target products, harsh process conditions, low safety, environmental pollution and high equipment requirements, and to provide a new preparation method of methylated aminocaprolactam and its application, and a cleaning / sterilization material. The preparation method only uses aminocaprolactam and / or its derivatives and methanol as a reaction system, does not contain an alkylating agent, and has the advantages of adjustable selectivity of the target product, a green and safe reaction process, and the like.
[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing methylated aminocaprolactam, comprising contacting aminocaprolactam and / or its derivatives with methanol in the presence of a catalyst and performing a methylation reaction to obtain methylated aminocaprolactam;
[0007] Wherein, the methylated aminocaprolactam includes methylaminocaprolactam and / or dimethylaminocaprolactam.
[0008] Preferably, the mass ratio of the aminocaprolactam and / or its derivatives to the catalyst is 1:0.1-10, preferably 1:0.1-5, more preferably 1:0.5-2.
[0009] Preferably, the usage ratio of the aminocaprolactam and / or its derivatives in g to the methanol in mL is 1:5-1000, preferably 1:20-500, more preferably 1:80-300.
[0010] Preferably, the catalyst is a metal supported catalyst, preferably a single-component supported catalyst, a two-component supported catalyst, and more preferably a two-component supported catalyst.
[0011] Preferably, the two-component supported catalyst comprises a carrier, and a first active component and a second active component supported on the carrier, wherein the first active component and the second active component exist in the form of an alloy.
[0012] Preferably, based on the total weight of the dual-component supported catalyst, the content of the first active component is 0.1-10 wt%, preferably 0.2-5 wt%; the content of the second active component is 0.1-20 wt%, preferably 0.5-10 wt%.
[0013] Preferably, the carrier is selected from oxides and / or modified oxides, and the oxide is selected from Al 2 O 3 、SiO 2 、TiO 2 、ZrO 2 and CeO 2At least one of the above, the modified oxide is selected from silicon-modified alumina.
[0014] Preferably, when the carrier is selected from silicon-modified alumina, the B acid density of the silicon-modified alumina is ≤2 μmol / g, preferably 0-2 μmol / g, further preferably 0-1.4 μmol / g, and more preferably 0-0.5 μmol / g.
[0015] The second aspect of the present invention provides a use of methylated aminocaprolactam prepared by the preparation method provided in the first aspect as a polymerization monomer in the preparation of cleaning / sterilization materials, modified nylon materials, and long-chain branched polymer materials.
[0016] The third aspect of the present invention provides a cleaning / sterilization material, wherein the cleaning / sterilization material comprises methylated aminocaprolactam obtained by the preparation method provided in the first aspect.
[0017] Through the above technical scheme, the present invention provides a novel preparation method of methylated aminocaprolactam. Only aminocaprolactam and / or its derivatives and methanol exist in the reaction system, and no other alkylating agents such as aldehyde compounds and halogenated compounds are present. In combination with a catalyst, the synthetic route has the characteristics of adjustable selectivity of the target product, high novelty, green safety, etc., especially by regulating the carrier and active components in the catalyst, limiting the physical property parameters of the specific carrier and the specific structure of the active component, the selectivity of the target product is further improved; at the same time, the preparation method simplifies the process flow, is simple to operate, is environmentally friendly, and is convenient for industrial production.
[0018] The methylated aminocaprolactam provided by the present invention can be used as a polymerization monomer to prepare cleaning / sterilization materials, modified nylon materials, long-chain branched polymerization materials, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a synthetic route for methylated aminocaprolactam provided by the present invention;
[0020] Figure 2 is a SEM image of the silicon-modified alumina AS-1 prepared in Preparation Example 1;
[0021] Figure 3 It is the pyridine infrared characterization spectrum of the silicon-modified alumina AS-1 prepared in Preparation Example 1 and the formed alumina DS-1 prepared in Preparation Example 15;
[0022] Figure 4 (a) is the transmission infrared spectrum of the silicon-modified alumina AS-1 obtained in Preparation Example 1;
[0023] Figure 4 (b) is the transmission infrared spectrum of the formed alumina DS-1 obtained in Preparation Example 15;
[0024] Figure 5 1. The spherical aberration transmission electron microscope image of the two-component supported catalyst PtIn / AS-1 prepared in Preparation Example 1 and the element distribution map of Pt and In;
[0025] Figure 6 is an EDS line scan spectrum of a single PtIn nanoparticle on the surface of the two-component supported catalyst PtIn / AS-1 prepared in Preparation Example 1;
[0026] Figure 7 It is the XRD spectra of the active components in the two-component supported catalyst PtIn / AS-1 prepared in Preparation Example 1 and the active components in the single-component supported catalyst Pt / AS-1 prepared in Preparation Example 16. DETAILED DESCRIPTION
[0027] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0028] In the present invention, unless otherwise specified, "first", "second", "third" and "fourth" do not indicate a sequence or limit the materials or steps, but are only used to distinguish that they are not the same material or step. For example, "first", "second", "third" and "fourth" in "first roasting", "second roasting", "third roasting" and "fourth roasting" are only used to indicate that they are not the same roasting; similarly, "first" and "second" in "first active component" and "second active component" are only used to indicate that they are not the same active component.
[0029] The first aspect of the present invention provides a method for preparing methylated aminocaprolactam, comprising contacting aminocaprolactam and / or its derivatives with methanol in the presence of a catalyst and performing a methylation reaction to obtain methylated aminocaprolactam;
[0030] Wherein, the methylated aminocaprolactam includes methylaminocaprolactam and / or dimethylaminocaprolactam.
[0031] The inventors of the present invention have found that: aminocaprolactam and / or its derivatives are directly contacted with methanol and subjected to a methylation reaction, methanol is used as both a reaction solvent and an alkylating agent, and the use of alkylating agents such as aldehyde compounds and halides is avoided, thereby providing a highly novel and green synthetic route; in combination with a catalyst, in particular, the catalyst is limited to a two-component supported catalyst, the two components are limited to exist in the form of an alloy, and in particular, a specific carrier is combined to achieve adjustable selectivity of the target product (methylaminocaprolactam and / or dimethylaminocaprolactam), thereby further effectively improving the selectivity of the target product.
[0032] In some embodiments of the present invention, preferably, the mass ratio of the aminocaprolactam and / or its derivatives to the catalyst is 1:0.1-10, for example, 1:0.1, 1:0.5, 1:1, 1:1.5, 1:2, 1:3, 1:5, 1:8, 1:10, and any value in the range of any two values, preferably 1:0.1-5, more preferably 1:0.5-2. The mass ratio meeting the above range further improves the conversion rate of aminocaprolactam and / or its derivatives.
[0033] In some embodiments of the present invention, preferably, the aminocaprolactam and / or its derivatives are selected from aminocaprolactam and / or aminocaprolactam salts. In the present invention, aminocaprolactam salts include but are not limited to hydrochlorides, sulfates, nitrates, and the like.
[0034] In some embodiments of the present invention, further preferably, the aminocaprolactam and / or its derivatives are selected from at least one of DL-α-amino-ε-caprolactam, DL-α-amino-ε-caprolactam hydrochloride, DL-α-amino-ε-caprolactam sulfate and DL-α-amino-ε-caprolactam nitrate.
[0035] In some embodiments of the present invention, preferably, the amount ratio of the aminocaprolactam and / or its derivatives in g to the methanol in mL is 1:5-1000, for example, 1:5, 1:10, 1:20, 1:30, 1:40, 1:50, 1:80, 1:100, 1:150, 1:200, 1:250, 1:300, 1:500, 1:1000, and any value in the range composed of any two values, preferably 1:20-500, more preferably 1:80-300.
[0036] In some embodiments of the present invention, preferably, the conditions of the methylation reaction include: temperature of 50-180°C, time of 0.5-24h, and pressure of 0.1-10MPa; further preferably, the conditions of the methylation reaction include: temperature of 60-120°C, time of 1-5h, and pressure of 0.5-2MPa. The preferred methylation reaction conditions are more conducive to improving the conversion rate of raw materials and the selectivity of target products. In the present invention, pressure refers to gauge pressure. In the present invention, the atmosphere of the methylation reaction includes but is not limited to nitrogen, hydrogen, argon, etc.
[0037] In some embodiments of the present invention, preferably, the catalyst is a metal supported catalyst, preferably a single-component supported catalyst, a two-component supported catalyst, and more preferably a two-component supported catalyst. The use of a preferred catalyst type is more conducive to improving the selectivity of the target product.
[0038] In some embodiments of the present invention, preferably, the catalyst is a single-component supported catalyst, and the single-component supported catalyst comprises: a carrier and an active component supported on the carrier; further preferably, based on the total weight of the single-component supported catalyst, the content of the active component is 0.1-10wt%, preferably 0.2-5wt%; more preferably, the carrier is selected from Al 2 O 3 、SiO 2 、TiO 2 、ZrO 2 、CeO 2 and at least one of silicon-modified alumina, preferably silicon-modified alumina, and the active component is selected from at least one of Pd, Pt, Ru, Ir and Rh, preferably Pd and / or Pt. The catalyst meeting the above conditions has better catalytic dehydrogenation performance and effectively improves the catalytic activity of the single-component supported catalyst.
[0039] In some embodiments of the present invention, preferably, the catalyst is a two-component supported catalyst, which includes a carrier, and a first active component and a second active component supported on the carrier, wherein the first active component and the second active component exist in the form of an alloy. A catalyst that meets the above conditions has better catalytic dehydrogenation performance and more effectively improves the catalytic activity of the two-component supported catalyst.
[0040] In the present invention, in the two-component supported catalyst, the first active component and the second active component exist in the form of an alloy, which means that the first active component and the second active component are supported on the carrier in the form of a metal mixture.
[0041] In a preferred embodiment of the present invention, when the catalyst is a two-component supported catalyst, and the two components exist in the form of an alloy, the synthesis route of methylated aminocaprolactam is as follows: Figure 1 As shown, the overall reaction path is: in the presence of a two-component supported catalyst, aminocaprolactam and methanol undergo a methylation reaction to obtain methylated aminocaprolactam, that is, methylaminocaprolactam and / or dimethylaminocaprolactam; specifically, in the first step, methanol is converted into formaldehyde by dehydrogenation in the presence of a two-component supported catalyst; in the second step, the formaldehyde and aminocaprolactam react to obtain a first intermediate; in the third step, the first intermediate and methanol undergo a dehydrogenation reaction to obtain methylaminocaprolactam; in the fourth step, the methylaminocaprolactam and formaldehyde undergo a methylation reaction to obtain a second intermediate; in the fifth step, the second intermediate and methanol undergo a dehydrogenation reaction to obtain dimethylaminocaprolactam. Therefore, in the present invention, methanol is used as both a solvent and an alkylating agent.
[0042] In some embodiments of the present invention, preferably, based on the total weight of the two-component supported catalyst, the first active component content is 0.1-10wt%, for example, 0.1wt%, 0.2wt%, 0.5wt%, 1wt%, 2wt%, 5wt%, 10wt%, and any value in the range of any two values, preferably 0.2-5wt%; the second active component content is 0.1-20wt%, for example, 0.1wt%, 0.2wt%, 0.5wt%, 1wt%, 2wt%, 5wt%, 10wt%, 15wt%, 20wt%, and any value in the range of any two values, preferably 0.5-10wt%. The preferred conditions are more conducive to improving the catalytic activity and selectivity of the two-component supported catalyst.
[0043] In some embodiments of the present invention, preferably, in the two-component supported catalyst, the first active component is selected from noble metal elements, preferably selected from at least one of Pd, Pt, Ru, Ir and Rh, more preferably selected from Pd and / or Pt. The use of preferred conditions is more conducive to improving the catalytic activity of the two-component supported catalyst, that is, improving the conversion rate of the raw material and the selectivity of the target product, thereby improving the yield of the target product.
[0044] In some embodiments of the present invention, preferably, in the two-component supported catalyst, the second active component is selected from non-precious metal elements, preferably selected from at least one of Ni, Co, In, Sn, Ga, Zn, Mn and Fe, and more preferably selected from at least one of Ni, In, Ga and Zn.
[0045] In some embodiments of the present invention, preferably, in the two-component supported catalyst, the carrier is selected from oxides and / or modified oxides, and the oxide is selected from Al 2 O 3 、SiO 2 、TiO 2 、ZrO 2 and CeO 2 At least one of; the modified oxide is selected from silicon-modified alumina.
[0046] In the present invention, silicon is loaded on the surface of alumina, and silicon is limited to be connected to the surface of alumina through Si-O-Al chemical bonds, and adjacent silicon on the surface of the alumina is limited to be connected through Si-O-Si chemical bonds. Under the premise of ensuring that the modified alumina has a low wear index, high crushing strength, high specific surface area and low average pore size, the acid sites on the surface of alumina can be effectively masked, and the B acid density on the surface of silicon-modified alumina can be regulated, so that the B acid density of silicon-modified alumina is ≤2μmol / g. At the same time, the silicon-modified alumina with low B acid density is used as a carrier, and then combined with the first active component and the second active component in the form of an alloy, so that the two-component supported catalyst has a low B acid density and has better catalytic dehydrogenation performance, thereby effectively improving the catalytic activity of the two-component supported catalyst and obtaining a high yield of the target product.
[0047] In some embodiments of the present invention, preferably, when the carrier is selected from silicon-modified alumina, the B acid density of the silicon-modified alumina is ≤2 μmol / g, for example, 0 μmol / g, 0.1 μmol / g, 0.2 μmol / g, 0.3 μmol / g, 0.5 μmol / g, 0.8 μmol / g, 1 μmol / g, 1.4 μmol / g, 1.5 μmol / g, 2 μmol / g, and any value in the range composed of any two values, preferably 0-2 μmol / g, further preferably 0-1.4 μmol / g, and more preferably 0-0.5 μmol / g.
[0048] In the present invention, unless otherwise specified, B acid density refers to Acid density.
[0049] In the present invention, the B acid density parameter is calculated based on the amount of pyridine desorbed by temperature increase; B acid density = the amount of acid of silicon-modified alumina measured by infrared spectrum of pyridine (in μmol) / the mass of silicon-modified alumina (in g).
[0050] In a preferred embodiment of the present invention, the catalyst is selected from a two-component supported catalyst, comprising a carrier, and a first active component and a second active component supported on the carrier, wherein the carrier is silicon-modified alumina with a B acid density of ≤2 μmol / g, and the first active component and the second active component exist in the form of an alloy.
[0051] In some embodiments of the present invention, preferably, the silicon-modified alumina comprises silicon and alumina, wherein the silicon-alumina ratio of the silicon-modified alumina is less than 1, the silicon is connected to the surface of the alumina via a Si-O-Al chemical bond, and adjacent silicon on the surface of the alumina is connected via a Si-O-Si chemical bond. In the present invention, the connection mode between Si, Al, and O in the silicon-modified alumina is measured by solid transmission infrared.
[0052] In the present invention, unless otherwise specified, the connection of silicon to the surface of the aluminum oxide via Si-O-Al chemical bonds means that Si and Al in the aluminum oxide share a common portion of O, thereby anchoring silicon in the form of SiOx to the surface of the aluminum oxide.
[0053] In some embodiments of the present invention, preferably, based on the total weight of the silicon-modified alumina, the content of the alumina is 50-90wt%, preferably 70-80wt%; x The silicon content is 10-50wt%, preferably 20-30wt%, wherein 1≤x≤2. The preferred conditions are more conducive to reducing the B acid density of the modified alumina.
[0054] In the present invention, unless otherwise specified, the silicon-modified alumina contains no other impurities except silicon and alumina, that is, the sum of the contents of silicon and alumina in the silicon-modified alumina is 100 wt%.
[0055] In some embodiments of the present invention, preferably, the shape of the silicon-modified alumina is selected from spherical and strip-shaped, wherein the spherical shape includes but is not limited to microspheres and small balls.
[0056] In some embodiments of the present invention, preferably, the aluminum oxide is selected from γ-alumina. The use of the preferred conditions is more conducive to improving the activity of silicon-modified aluminum oxide.
[0057] In some embodiments of the present invention, preferably, the specific surface area of the silicon-modified alumina is 100-220 m 2 / g, preferably 120-200m 2 / g; average pore size is 10-30nm, preferably 15-25nm; wear index is 1-20%, preferably 1-15%; crushing strength is 50-150N / cm, preferably 70-130N / cm. In the present invention, unless otherwise specified, the specific surface area parameter is measured by a fully automatic isothermal adsorption instrument; the average pore size parameter is obtained by a fully automatic isothermal adsorption instrument in combination with the BJH model; the wear index parameter is measured by a wear index analyzer; and the crushing strength parameter is measured by a particle strength tester.
[0058] In the present invention, the source of the silicon-modified alumina has a wide selection range, as long as the silicon-modified alumina meets the above definition. Preferably, the silicon-modified alumina is prepared by the following method:
[0059] S1, performing a first mixing of an aluminum source, an acidic compound and water, and sequentially performing molding, a first drying and a first calcination on the obtained first mixture to obtain molded alumina;
[0060] S2, dissolving the shaped alumina in water, first adding an alkaline compound to adjust the pH to 7-12, and then adding a silicon source for a second mixing to obtain a second mixture;
[0061] S3, subjecting the second mixture to solid-liquid separation, and subjecting the obtained modified alumina precursor to a second drying and a second calcination in sequence to obtain the silicon-modified alumina.
[0062] In some embodiments of the present invention, preferably, in step S1, the content of the aluminum source in the first mixture is 0.01-10wt%, preferably 0.05-5wt%; the content of the acidic compound is 0.01-3wt%, preferably 0.05-1wt%. In the present invention, the feed amount / dosage ratio of the aluminum source, the acidic compound and water meets the above definition.
[0063] In the present invention, the type of the aluminum source has a wide selection range. Preferably, the aluminum source is a soluble aluminum salt, including but not limited to γ-alumina, aluminum oxide hydroxide, pseudo-boehmite, aluminum chloride, aluminum nitrate, etc. When the aluminum source is selected from γ-alumina, step S1 acidifies the surface of the powdered aluminum oxide to form a hydrated hydroxyl state, which is convenient for the subsequent addition of alkaline compounds and silicon sources for silicon modification.
[0064] In the present invention, the type of the acidic compound has a wide selection range. Preferably, the acidic compound is selected from at least one of hydrochloric acid, nitric acid, sulfuric acid and phosphoric acid. In the present invention, the acidic compound exists in the form of an aqueous solution, and preferably the concentration of the acidic compound in the acidic compound solution is 1-50wt%.
[0065] In the present invention, the first mixing method has a wide range of selection, as long as the aluminum source, the acidic compound and water are mixed. Preferably, in step S1, the first mixing conditions include: temperature of 15-40°C, preferably 20-30°C; rotation speed of 100-1000rpm, preferably 300-1000rpm; time of 0.1-5h, preferably 0.1-2h.
[0066] In the present invention, there is a wide range of choices for the molding method. In step S1, the molding method includes but is not limited to oil-ammonia drop ball molding, spray drying molding, extrusion molding, etc.
[0067] In the present invention, the first drying is to remove water from the first mixture. Preferably, in step S1, the first drying conditions include: temperature of 80-120°C, time of 90-110°C, and time of 1-20h, preferably 1-12h.
[0068] In the present invention, the first drying method has a wide range of options, as long as the conditions of the first drying meet the above-mentioned limitations. Preferably, the first drying method includes but is not limited to spray drying, blast drying, vacuum drying, etc.
[0069] In some embodiments of the present invention, preferably, in step S1, the conditions of the first calcination include: a temperature of 700-1200°C, preferably 800-1000°C; a time of 1-10h, preferably 1-5h. In the present invention, the first calcination is carried out in a muffle furnace or a tube furnace, and the calcination atmosphere is a non-reducing gas, preferably at least one of air, nitrogen and argon.
[0070] In the present invention, in step S2, the shaped alumina is first dissolved in water, an alkaline compound is added to adjust the pH, and then a silicon source is added for a second mixing, in order to obtain polyhydroxy silicic acid and / or hydroxy hydrated silicon.
[0071] In some embodiments of the present invention, preferably, in step S2, the pH is adjusted to 8-12, for example, 8, 9, 10, 10.5, 11.5, 12, and any value in the range consisting of any two values, preferably 10.5-11.5.
[0072] In some embodiments of the present invention, preferably, in step S2, Al 2 O 3 The molded alumina and SiO x The weight ratio of the silicon source is 5-9:1-5, for example, 5:5, 7:3, 8:2, 9:1, and any value in the range of any two values, preferably 7-8:2-3; wherein 1≤x≤2.
[0073] In some embodiments of the present invention, preferably, in step S2, the alkaline compound is selected from at least one of ammonium carbonate, ammonium bicarbonate and ammonia water.
[0074] In the present invention, the type of the silicon source has a wide range of choices. Preferably, in step S2, the silicon source is a soluble silicon salt, preferably selected from organic silicon salts and / or inorganic silicon salts, including but not limited to at least one of tetraethyl orthosilicate, tetramethylsilicon, silicon oxide aerogel and silicon tetrachloride.
[0075] In the present invention, unless otherwise specified, solubility means being easily soluble in water, or being easily soluble in water with the help of an auxiliary agent.
[0076] In some embodiments of the present invention, preferably, in step S2, the conditions for the second mixing include: temperature of 20-70°C, preferably 25-60°C; rotation speed of 100-1000rpm, preferably 300-1000rpm; time of 1-20h, preferably 6-12h.
[0077] In the present invention, the solid-liquid separation method has a wide range of selection, as long as the second mixture is subjected to solid-liquid separation to obtain a modified alumina precursor; the solid-liquid separation method includes but is not limited to filtration, sedimentation, etc.
[0078] In the present invention, the second drying is intended to remove the residual moisture in the modified alumina precursor. Preferably, in step S3, the second drying conditions include: temperature of 80-120°C, time of 90-110°C, and time of 1-20h, preferably 1-12h.
[0079] In the present invention, the second drying method has a wide range of options, as long as the second drying conditions meet the above-mentioned limitations. Preferably, the second drying method includes but is not limited to spray drying, blast drying, vacuum drying, etc.
[0080] In some embodiments of the present invention, preferably, in step S3, the conditions of the second calcination include: a temperature of 400-1000°C, preferably 500-900°C; a time of 1-10h, preferably 1-5h. In the present invention, the second calcination is carried out in a muffle furnace or a tubular furnace, and the calcination atmosphere is a non-reducing gas, preferably at least one of air, nitrogen and argon.
[0081] In some embodiments of the present invention, preferably, the two-component supported catalyst is prepared by the following method:
[0082] (I-1) loading a first soluble metal salt on the surface of the carrier, and sequentially performing a third drying and a third calcination on the obtained first intermediate to obtain a single-component supported catalyst; (I-2) loading a second soluble metal salt on the surface of the single-component supported catalyst, and sequentially performing a fourth drying and a fourth calcination on the obtained second intermediate to obtain the dual-component supported catalyst;
[0083] or,
[0084] (II) loading the first soluble metal salt and the second soluble metal salt on the surface of the carrier, and sequentially subjecting the obtained third intermediate to a fifth drying and a fifth calcination to obtain the dual-component supported catalyst;
[0085] Wherein, the third calcination, the fourth calcination and the fifth calcination are each independently performed in a hydrogen-containing atmosphere.
[0086] In the present invention, unless otherwise specified, there are two methods for preparing the dual-component supported catalyst: (I) firstly loading a first soluble metal salt on the surface of a carrier, and after a third drying and a third calcination, the surface of the obtained single-component supported catalyst is loaded with a second soluble metal salt, and after a fourth drying and a fourth calcination, a dual-component supported catalyst is obtained; (II) directly loading a first soluble metal salt and a second soluble metal salt on the surface of a carrier, and directly after a fifth drying and a fifth calcination, a dual-component supported catalyst is obtained, wherein the third calcination, the fourth calcination and the fifth calcination are all carried out in a hydrogen-containing atmosphere.
[0087] In some embodiments of the present invention, preferably, the hydrogen content in the hydrogen-containing atmosphere is ≥ 10% by volume, for example, 60% by volume, 70% by volume, 80% by volume, 90% by volume, 100% by volume, and any value in the range of any two values, preferably 20-90% by volume. When the hydrogen content in the hydrogen-containing atmosphere is less than 10%, the alloy morphology of the two-component catalyst is not ideal.
[0088] In some embodiments of the present invention, preferably, the hydrogen-containing atmosphere also contains an inert gas, wherein the inert gas includes but is not limited to nitrogen, helium, etc., preferably nitrogen; further preferably, the volume ratio of hydrogen to inert gas in the hydrogen-containing atmosphere is 1-9:9-1, for example, 1:9, 2:8, 3:7, 4:6, 6:4, 7:3, 8:2, 9:1, and any value in the range composed of any two numerical values, preferably 2-9:8-1.
[0089] In a preferred embodiment of the present invention, preferably, the hydrogen-containing atmosphere comprises hydrogen and nitrogen, and the volume ratio of hydrogen to nitrogen is 2-9:8-1.
[0090] In a preferred embodiment of the present invention, preferably, the loading amount of the first soluble metal salt in terms of metal element is 0.1-10wt%, preferably 0.2-5wt%. In the present invention, unless otherwise specified, the loading amount parameters are based on the total weight of the two-component supported catalyst.
[0091] In a preferred embodiment of the present invention, preferably, the loading amount of the second soluble metal salt calculated as the metal element is 0.1-20 wt %, preferably 0.5-10 wt %.
[0092] In the present invention, in step (I-1), step (I-2) and step (II), the loading method of the first soluble metal salt, the second soluble metal salt, and the first soluble metal salt and the second soluble metal salt has a wide range of selection, as long as the loading amount of the soluble metal salt meets the above definition. Preferably, the loading method is selected from the impregnation method and the sedimentation precipitation method.
[0093] In the present invention, in step (I-1), step (I-2) and step (II), when the loading method is impregnation, an impregnation solution containing a soluble metal salt needs to be prepared, and according to the amount of the impregnation solution, the impregnation method is selected from the excess impregnation method and the saturation impregnation method; according to the way the impregnation is implemented, the impregnation method is selected from the immersion impregnation method and the spray impregnation method. It is easy for those skilled in the art to understand that a catalyst with a specific loading amount can be obtained by adjusting and controlling the concentration, amount or amount of the impregnation solution.
[0094] In some embodiments of the present invention, in step (I-1), step (I-2) and step (II), when the loading method is an impregnation method, the solvent in the impregnation solution containing the soluble metal salt includes but is not limited to water, ammonia water, and hydrochloric acid. The present invention does not limit the concentration of the soluble metal salt in the impregnation solution containing the soluble metal salt.
[0095] In some embodiments of the present invention, in step (I-1), step (I-2) and step (II), when the loading method is a deposition precipitation method, the solvent in the impregnation solution containing the soluble metal salt includes but is not limited to water. The present invention does not limit the concentration of the soluble metal salt in the impregnation solution containing the soluble metal salt.
[0096] In some embodiments of the present invention, preferably, the first soluble metal salt is selected from hydrochloride, sulfate, nitrate, acetate containing at least one of Pt, Pd, Rh, Ir and Ru, preferably selected from hydrochloride, sulfate, nitrate, acetate containing Pd and / or Pt. In the present invention, the first soluble metal salt includes but is not limited to PdCl 2 , H 2PtCl 6 、Pd(NO 3 ) 2 、RuCl 3 , iridium acetate.
[0097] In some embodiments of the present invention, preferably, the second soluble metal salt is selected from hydrochloride, sulfate, nitrate, acetate containing at least one of Ni, Co, In, Sn, Ga, Zn, Mn, Fe, preferably selected from hydrochloride, sulfate, nitrate, acetate containing at least one of Ni, In, Ga and Zn. In the present invention, the soluble metal salt includes but is not limited to In(NO 3 ) 2 ,Ga(NO 3 ) 2 、NiCl 2 、Mn(NO 3 ) 2 、FeCl 3 .
[0098] In the present invention, in step (I-1), the first intermediate includes a carrier and a first soluble metal salt loaded on the carrier; the third drying is intended to remove the residual solvent in the first intermediate; the third calcination is intended to reduce the first soluble metal salt to a first metal element in a hydrogen-containing atmosphere to obtain a single-component supported catalyst (including a carrier and a first active component loaded on the surface of the carrier).
[0099] In the present invention, in step (I-2), the second intermediate includes a single-component supported catalyst and a second soluble metal salt supported on the single-component supported catalyst; the fourth drying is intended to remove the residual solvent in the second intermediate; the fourth calcination is intended to reduce the second soluble metal salt to a second metal element in a hydrogen-containing atmosphere, and to form an alloy state with the first metal element and the second metal element, thereby obtaining a two-component supported catalyst (including a carrier and a first active component and a second active component loaded on the surface of the carrier).
[0100] In the present invention, in step (II), the third intermediate includes a carrier and a first soluble metal salt and a first soluble metal salt loaded on the carrier; the fifth drying is intended to remove the residual solvent in the third intermediate; the fifth calcination is intended to reduce the first soluble metal salt and the second soluble metal salt to a first metal element and a second metal element respectively in a hydrogen-containing atmosphere, and exist in the form of an alloy, to obtain a two-component supported catalyst (including a carrier and a first active component and a second active component loaded on the surface of the carrier).
[0101] In some embodiments of the present invention, preferably, the conditions of the third drying, the fourth drying and the fifth drying each independently include: a temperature of 80-120°C, a time of 90-110°C, and a time of 1-20 hours, preferably 1-12 hours. In the present invention, the methods of the third drying, the fourth drying and the fifth drying include but are not limited to spray drying, blast drying, vacuum drying, etc.
[0102] In some embodiments of the present invention, preferably, the conditions of the third calcination, the fourth calcination and the fifth calcination each independently include: a temperature of 400-800°C, a time of 450-750°C, and a time of 1-10 hours, preferably 1-5 hours. In the present invention, the third calcination, the fourth calcination and the fifth calcination are carried out in a muffle furnace or a tubular furnace, and the calcination atmosphere is a hydrogen-containing atmosphere.
[0103] In some embodiments of the present invention, preferably, the morphology of the dual-component supported catalyst is selected from spherical and strip-shaped, wherein the spherical shape includes but is not limited to microspheres and small balls.
[0104] In the present invention, unless otherwise specified, the macroscopic morphology of the catalyst is measured using a scanning electron microscope; the morphology of the two-component alloy loaded on the catalyst surface is measured using an X-ray diffractometer and an elemental energy spectrum scanning accessory of a spherical aberration transmission electron microscope.
[0105] The second aspect of the present invention provides a use of methylated aminocaprolactam prepared by the preparation method provided in the first aspect as a polymerization monomer in the preparation of cleaning / sterilization materials, modified nylon materials, and long-chain branched polymer materials.
[0106] The third aspect of the present invention provides a cleaning / sterilization material, which comprises: methylated aminocaprolactam prepared by the preparation method provided in the first aspect.
[0107] According to a particularly preferred embodiment of the present invention, a method for preparing methylated aminocaprolactam comprises contacting aminocaprolactam and / or its derivatives with methanol in the presence of a two-component supported catalyst and performing a methylation reaction to obtain methylated aminocaprolactam;
[0108] Wherein, the methylated aminocaprolactam includes methylaminocaprolactam and / or dimethylaminocaprolactam;
[0109] The two-component supported catalyst comprises a carrier, and a first active component and a second active component supported on the carrier, wherein the first active component and the second active component exist in the form of an alloy; the carrier is selected from silicon-modified alumina with a B acid density of 0-0.5 μmol / g; the first active component is selected from Pd and / or Pt; the second active component is selected from at least one of Ni, In, Ga and Zn;
[0110] The silicon-modified alumina comprises silicon and alumina, wherein the silicon-to-alumina ratio of the silicon-modified alumina is less than 1, the silicon is connected to the surface of the alumina through a Si-O-Al chemical bond, and adjacent silicon on the surface of the alumina is connected through a Si-O-Si chemical bond; based on the total weight of the silicon-modified alumina, the content of the alumina is 70-80wt%; SiO x The silicon content is 20-30wt%, wherein 1≤x≤2; the specific surface area of the silicon-modified alumina is 120-200m 2 / g; average pore size is 15-25nm; wear index is 1-15%; crushing strength is 70-130N / cm;
[0111] The conditions of the methylation reaction include: temperature of 60-120° C., time of 1-5 h, and pressure of 0.5-2 MPa.
[0112] The present invention will be described in detail below through examples.
[0113] The B acid density parameter is calculated based on the amount of pyridine desorbed by temperature increase; that is, B acid density = the amount of acid of silicon-modified alumina tested by pyridine infrared spectrum (in μmol) / the mass of silicon-modified alumina (in g).
[0114] The connection mode between Si, Al and O in silicon-modified alumina was measured by solid transmission infrared;
[0115] The specific surface area parameters were measured using a fully automatic isothermal adsorption instrument;
[0116] The average pore size parameters were obtained using a fully automatic isothermal adsorption instrument and the BJH model.
[0117] Wear index parameters were measured using a wear index analyzer;
[0118] The crushing strength parameters were measured using a particle strength tester;
[0119] The macroscopic morphology of the silicon-modified alumina / bicomponent supported catalyst was measured by scanning electron microscopy;
[0120] The alloy morphology of the two components in the two-component supported catalyst was measured using an X-ray diffractometer and an elemental energy spectrum scanning accessory of a spherical aberration transmission electron microscope.
[0121] Preparation Examples 1-18 are used to prepare catalysts. The physical properties of the carriers are listed in Table 1, and the physical properties of the catalysts are listed in Table 2.
[0122] Preparation Example 1
[0123] (1) 80 g of an aluminum source (pseudo-boehmite), 5 g of an acidic compound (30 wt % dilute nitric acid) and 800 mL of water were first mixed in a 1500 mL stirred tank (temperature: 25° C., rotation speed: 600 rpm, time: 1 h) to obtain a first mixture;
[0124] The first mixture was spray-dried (temperature: 100° C., time: 5 h), and then calcined in a muffle furnace at 800° C. for 3 h in static air to obtain microspherical aluminum oxide.
[0125] (2) dissolving the above-mentioned shaped alumina in 800 mL of water, first adding an alkaline compound (ammonia water) to adjust the pH to 10, and then adding 60 g of a silicon source (ethyl orthosilicate) for a second mixing (temperature of 25° C., rotation speed of 600 rpm, time of 12 h) to obtain a second mixture;
[0126] (3) subjecting the second mixture to solid-liquid separation, and drying the obtained modified alumina precursor in a vacuum drying oven at 100° C. for 5 h, and then calcining in a muffle furnace at 600° C. for 3 h in a static air atmosphere to obtain microspherical silicon-modified alumina AS-1;
[0127] The SEM image of the silicon-modified alumina AS-1 is as follows: Figure 2 As shown by Figure 2 It can be seen that the silicon-modified alumina AS-1 has a microspherical morphology;
[0128] Among them, the pyridine infrared characterization spectrum of the above silicon-modified alumina AS-1 is as follows Figure 3 As shown by Figure 3 It can be seen that the silicon-modified alumina AS-1 has an extremely low number of B acid sites, and the B acid density is 0 μmol / g;
[0129] The transmission infrared spectrum of the silicon-modified alumina AS-1 is as follows: Figure 4 As shown in (a), Figure 4 (a) It can be seen that the wave number is 1066cm -1 and 1160cm -1 The signal peaks at the positions are the vibration absorption peaks of Si-O-Si and Si-O-Al bonds, indicating that the silicon in the silicon-modified alumina AS-1 is bonded to the alumina through chemical bonds, and the adjacent silicon on the surface of the alumina is in the form of SiOx (1≤x≤2) exists in the form of clusters.
[0130] (4) H 2 PtCl 6 The solution was impregnated onto the surface of the silicon-modified alumina AS-1 by an over-impregnation method to obtain a first intermediate with a Pt loading of 5 wt%. The first intermediate was dried at 100 °C for 5 h in a vacuum drying oven and then heated to room temperature in a muffle furnace under a static H 2 The catalyst was calcined at 500 °C for 3 h in an atmosphere to obtain a single-component supported catalyst.
[0131] WillIn(NO 3 ) 3 The solution was impregnated onto the surface of the above-mentioned single-component supported catalyst by saturation impregnation method to obtain a second intermediate with an In loading of 2 wt%. After drying at 80°C for 12 h in a forced air drying oven, the catalyst was dried in a tube furnace H 2 The catalyst was calcined at 600°C for 4 h in an atmosphere to obtain a microspherical two-component supported catalyst PtIn / AS-1, in which Pt and In existed in an alloy state.
[0132] The spherical aberration transmission electron microscopy image and the element distribution map of Pt and In of the above-mentioned two-component supported catalyst PtIn / AS-1, the EDS line scan spectrum and XRD spectrum of the surface single PtIn nanoparticles are shown as follows: Figure 5-7 As shown by Figure 5-7 It can be seen that in the above two-component supported catalyst PtIn / AS-1, Pt and In are supported on the surface of silicon-modified alumina AS-1, and Pt and In exist in the form of an alloy.
[0133] Preparation Example 2
[0134] (1) 50 g of an aluminum source (pseudo-boehmite), 10 g of an acidic compound (5 wt % dilute nitric acid) and 800 mL of water were first mixed in a 1500 mL stirred tank (temperature: 20° C., rotation speed: 500 rpm, time: 1 h) to obtain a first mixture;
[0135] The first mixture was spray-dried (temperature: 100° C., time: 5 h), and then calcined in a muffle furnace at 1000° C. for 1 h in static air to obtain microspherical aluminum oxide.
[0136] (2) dissolving the above-mentioned shaped alumina in 800 mL of water, first adding an alkaline compound (ammonium bicarbonate) to adjust the pH to 9, and then adding 50 g of a silicon source (silicon oxide aerogel) for a second mixing (temperature of 25° C., rotation speed of 500 rpm, time of 8 h) to obtain a second mixture;
[0137] (3) subjecting the second mixture to solid-liquid separation, and drying the obtained modified alumina precursor in a vacuum drying oven at 100° C. for 5 h, and then calcining in a tubular furnace at 800° C. for 2 h in a nitrogen atmosphere to obtain microspherical silicon-modified alumina AS-2;
[0138] (4) Pd(NH 3 ) 4 (NO 3 ) 2 The solution was impregnated onto the surface of the silicon-modified alumina AS-2 by an over-impregnation method to obtain a first intermediate with a Pd loading of 6 wt%. The first intermediate was dried at 100 °C for 5 h in a vacuum oven and then heated to room temperature in a muffle furnace under static H 2 The catalyst was calcined at 500 °C for 3 h to obtain a single-component supported catalyst.
[0139] Will Zn(NO 3 ) 2 The solution was impregnated onto the surface of the above-mentioned single-component supported catalyst by saturation impregnation method to obtain a second intermediate with a Zn loading of 10 wt%, which was dried at 80°C for 12 h in a blast drying oven and then dried in a tubular furnace H 2 and N 2 Mixed atmosphere (H 2 and N 2 The catalyst was calcined at 600 °C for 4 h in a volume ratio of 2:8 to obtain a microspherical two-component supported catalyst PdZn / AS-2, in which Pd and Zn exist in the form of an alloy.
[0140] Preparation Example 3
[0141] (1) 20 g of an aluminum source (aluminum oxyhydroxide), 1 g of an acidic compound (30 wt % dilute hydrochloric acid) and 800 mL of water were first mixed in a 1500 mL stirred tank (temperature: 30° C., rotation speed: 500 rpm, time: 1 h) to obtain a first mixture;
[0142] The first mixture is extruded, dried with blast air (temperature is 100° C., time is 5 h), and then calcined in a muffle furnace at 800° C. for 3 h to obtain strip-shaped aluminum oxide;
[0143] (2) dissolving the above-mentioned shaped alumina in 800 mL of water, first adding an alkaline compound (ammonia water) to adjust the pH to 10, and then adding 56 g of a silicon source (silicon tetrachloride) for a second mixing (temperature of 50° C., rotation speed of 500 rpm, time of 10 h) to obtain a second mixture;
[0144] (3) The second mixture was subjected to solid-liquid separation, and the obtained modified alumina precursor was dried in a vacuum drying oven at 100° C. for 5 h, and then calcined in a tubular furnace at 600° C. for 6 h in a nitrogen atmosphere to obtain strip-shaped silicon-modified alumina AS-3;
[0145] (4) H 2 PtCl 6 The solution was impregnated onto the surface of the silicon-modified alumina AS-3 by saturated impregnation to obtain a first intermediate with a Pt loading of 2 wt%. The first intermediate was dried at 100 °C for 5 h in a vacuum oven and then heated in a tube furnace H 2 and N 2 Mixed atmosphere (H 2 and N 2 The catalyst was calcined at 500°C for 3 h in a volume ratio of 4:6 to obtain a single-component supported catalyst;
[0146] Will Ni(NO 3 ) 3 The solution was impregnated onto the surface of the above-mentioned single-component supported catalyst by saturation impregnation method to obtain a second intermediate with a Ni loading of 0.1 wt%. After being dried at 120° C. for 6 h in a forced air drying oven, the catalyst was dried in a tube furnace H 2 and N 2 Mixed atmosphere (H 2 and N 2 The catalyst was calcined at 750 °C for 4 h in a volume ratio of 4:6 to obtain a strip-shaped two-component supported catalyst PtNi / AS-3, in which Pt and Ni exist in an alloy form.
[0147] Preparation Example 4
[0148] (1) 50 g of an aluminum source (pseudo-boehmite), 2 g of an acidic compound (50 wt % dilute phosphoric acid) and 800 mL of water were first mixed in a 1500 mL stirred tank (temperature: 25° C., rotation speed: 800 rpm, time: 1 h) to obtain a first mixture;
[0149] The first mixture is formed into balls by drop molding, dried by blast drying (temperature is 100° C., time is 5 h), and then calcined in a muffle furnace at 800° C. for 2 h to obtain small spherical aluminum oxide;
[0150] (2) dissolving the above-mentioned shaped alumina in 800 mL of water, first adding an alkaline compound (ammonia water) to adjust the pH to 10, and then adding 48 g of a silicon source (ethyl orthosilicate) for a second mixing (temperature of 35° C., rotation speed of 500 rpm, time of 6 h) to obtain a second mixture;
[0151] (3) The second mixture is subjected to solid-liquid separation, and the obtained modified alumina precursor is dried at 100° C. for 5 h in a vacuum drying oven, and then calcined at 800° C. for 3 h in a muffle furnace in a static nitrogen atmosphere to obtain small spherical silicon-modified alumina AS-4;
[0152] (4) Pd(NH 3 ) 4 (NO 3 )2 The solution was impregnated onto the surface of the silicon-modified alumina AS-4 by an over-impregnation method to obtain a first intermediate with a Pd loading of 2 wt%. The first intermediate was dried at 100 °C for 5 h in a vacuum oven and then heated in a tube furnace H 2 and N 2 Mixed atmosphere (H 2 and N 2 The volume ratio is 1:9) and calcined at 500°C for 3h to obtain a single-component supported catalyst;
[0153] WillIn(NO 3 ) 3 The solution was impregnated onto the surface of the above-mentioned single-component supported catalyst by a deposition precipitation method to obtain a second intermediate with an In loading of 1 wt%. After being dried at 100°C for 8 h in a forced air drying oven, the catalyst was dried in a tubular furnace H 2 and N 2 Mixed atmosphere (H 2 and N 2 The catalyst was calcined at 600 °C for 4 h in a volume ratio of 4:6 to obtain a spherical two-component supported catalyst PdIn / AS-4, in which Pd and In exist in an alloy form.
[0154] Preparation Example 5
[0155] The method of Preparation Example 1 is followed, except that in step (4),
[0156] Pd(NH 3 ) 4 Cl 2 The solution was impregnated onto the surface of the silicon-modified alumina AS-1 by an over-impregnation method to obtain a first intermediate with a Pd loading of 6 wt%. The first intermediate was dried at 100 °C for 5 h in a vacuum oven and then heated to room temperature in a muffle furnace under static H 2 The catalyst was calcined at 500 °C for 3 h in an atmosphere to obtain a single-component supported catalyst.
[0157] WillIn(NO 3 ) 3 The solution was impregnated onto the surface of the above-mentioned single-component supported catalyst by saturation impregnation method to obtain a second intermediate with an In loading of 2 wt%. After drying at 80°C for 12 h in a forced air drying oven, the catalyst was dried in a tube furnace H 2 The catalyst was calcined at 600°C for 4 h in an atmosphere to obtain a microspherical two-component supported catalyst PdIn / AS-1, in which Pd and In existed in an alloy state.
[0158] Preparation Example 6
[0159] The method of Preparation Example 1 is followed, except that in step (4),
[0160] H 2 PtCl6 The solution was impregnated onto the surface of the silicon-modified alumina AS-1 by an over-impregnation method to obtain a first intermediate with a Pt loading of 10 wt%. The first intermediate was dried at 80 °C for 12 h in a vacuum drying oven and then heated in a muffle furnace at a static H 2 The catalyst was calcined at 600 °C for 3 h in an atmosphere to obtain a single-component supported catalyst.
[0161] Will Ga(NO 3 ) 3 The solution was impregnated onto the surface of the above-mentioned single-component supported catalyst by saturation impregnation method to obtain a second intermediate with a Ga loading of 3 wt%. After being dried at 120° C. for 3 h in a blast drying oven, the catalyst was dried in a tube furnace H 2 The catalyst was calcined at 600°C for 4 h in an atmosphere to obtain a microspherical dual-component supported catalyst PtGa / AS-1, in which Pt and Ga existed in an alloy state.
[0162] Preparation Example 7
[0163] The method of Preparation Example 1 is followed, except that in step (4),
[0164] H 2 PtCl 6 The solution was impregnated onto the surface of the silicon-modified alumina AS-1 by an excess impregnation method to obtain a first intermediate with a Pt loading of 5 wt%. After drying at 80 °C for 12 h in a vacuum drying oven, the first intermediate was dried in a muffle furnace at a temperature of 100 °C. 2 The catalyst was calcined at 600 °C for 3 h in an atmosphere to obtain a single-component supported catalyst.
[0165] The zinc acetate solution was impregnated onto the surface of the above-mentioned single-component supported catalyst by saturated impregnation method to obtain a second intermediate with a Zn loading of 10 wt%, which was dried at 120° C. for 3 h in a forced air drying oven and then dried in a tubular furnace H 2 The catalyst was calcined at 600°C for 4 h in an atmosphere to obtain a microspherical two-component supported catalyst PtZn / AS-1, in which Pt and Zn existed in an alloy state.
[0166] Preparation Example 8
[0167] The method of Preparation Example 1 is followed, except that in step (4),
[0168] Prepare H 2 PtCl 6 andIn(NO 3 ) 3 The mixed solution was impregnated into the modified silicon alumina AS-1 by excessive impregnation method to obtain a third intermediate with a Pt loading of 5wt% and an In loading of 2wt%, which was dried at 80°C for 12h in a blast drying oven and then heated in a tube furnace H 2After calcination at 600 °C for 4 h in an atmosphere, a microspherical two-component supported catalyst PtIn-co / AS-1 was obtained, in which Pt and In existed in the form of an alloy.
[0169] Preparation Example 9
[0170] H 2 PtCl 6 The solution was impregnated into Al by deposition precipitation method. 2 O 3 The surface of the first intermediate with a Pt loading of 2 wt% was obtained, and after drying at 100 °C for 6 h in a vacuum drying oven, the first intermediate was dried in a muffle furnace at a temperature of 100 °C for 6 h. 2 The catalyst was calcined at 500 °C for 3 h in an atmosphere to obtain a single-component supported catalyst.
[0171] SnCl 2 The solution was impregnated onto the surface of the above-mentioned single-component supported catalyst by a deposition precipitation method to obtain a second intermediate with a Sn loading of 1 wt%. After drying at 120°C for 3 h in a forced air drying oven, the catalyst was dried in a tubular furnace H 2 The dual-component supported catalyst PtSn / Al was obtained by calcining at 600 °C for 4 h in an atmosphere. 2 O 3 , wherein Pt and Sn exist in alloy form.
[0172] Preparation Example 10
[0173] Pd(NH 3 ) 4 (NO 3 ) 2 The solution was impregnated into ZrO 2 The surface of the first intermediate with a Pd loading of 6 wt% was obtained, and after drying at 120 °C for 3 h in a vacuum drying oven, the first intermediate was dried in a muffle furnace at a temperature of 1 000 nm and a temperature of 1 000 nm. 2 The catalyst was calcined at 400 °C for 3 h in an atmosphere to obtain a single-component supported catalyst.
[0174] Mn(NO 3 ) 2 The solution was impregnated onto the surface of the above-mentioned single-component supported catalyst by saturation impregnation method to obtain a second intermediate with a Mn loading of 20 wt%. After being dried at 100°C for 8 h in a blast drying oven, the catalyst was dried in a tubular furnace H 2 The dual-component supported catalyst PdMn / ZrO was obtained by calcining at 600℃ for 4h in an atmosphere. 2 , wherein Pd and Mn exist in alloy form.
[0175] Preparation Example 11
[0176] The iridium acetate solution was impregnated into the Al 2 O3 The first intermediate with an Ir loading of 2 wt% was obtained, and after drying at 100 °C for 6 h in a vacuum drying oven, the first intermediate was dried in a muffle furnace at a temperature of 100 °C for 6 h. 2 The catalyst was calcined at 500 °C for 3 h in an atmosphere to obtain a single-component supported catalyst.
[0177] CoCl 3 The solution was impregnated onto the surface of the above-mentioned single-component supported catalyst by saturation impregnation method to obtain a second intermediate with a Co loading of 0.1 wt%. After drying at 120° C. for 3 h in a forced air drying oven, the catalyst was dried in a tube furnace H 2 The bicomponent supported catalyst IrCo / Al was obtained by calcining at 800℃ for 6h in an atmosphere. 2 O 3 , wherein Ir and Co exist in alloy form.
[0178] Preparation Example 12
[0179] RhCl 3 The solution was impregnated into the SiO 2 The surface of the first intermediate with a Rh loading of 6 wt% was obtained, and the first intermediate was dried at 100 °C for 6 h in a vacuum oven and then heated to 400 °C in a muffle furnace. 2 The catalyst was calcined at 400 °C for 9 h in an atmosphere to obtain a single-component supported catalyst.
[0180] NiCl 2 The solution was impregnated onto the surface of the above-mentioned single-component supported catalyst by saturation impregnation method to obtain a second intermediate with a Ni loading of 2 wt%. After drying at 120°C for 3 h in a forced air drying oven, the catalyst was dried in a tube furnace H 2 The RhNi / SiO2 dual-component supported catalyst was calcined at 800 °C for 6 h in a molten-gas atmosphere. 2 , wherein Rh and Ni exist in alloy form.
[0181] Preparation Example 13
[0182] H 2 PtCl 6 The solution was impregnated into ZrO 2 The surface of the first intermediate with a Pt loading of 8 wt% was obtained, and the first intermediate was dried at 100 °C for 6 h in a vacuum drying oven and then heated to 40 °C in a muffle furnace. 2 The catalyst was calcined at 400 °C for 3 h in an atmosphere to obtain a single-component supported catalyst.
[0183] FeCl 3 The solution was impregnated onto the surface of the above-mentioned single-component supported catalyst by saturation impregnation method to obtain a second intermediate with an Fe loading of 3 wt%. After drying at 120°C for 3 h in a forced air drying oven, the catalyst was dried in a tube furnace H 2The dual-component supported catalyst PtFe / ZrO was obtained by calcining at 600℃ for 4h in an atmosphere. 2 , wherein Pt and Fe exist in alloy form.
[0184] Preparation Example 14
[0185] Pd(NH 3 ) 4 (NO 3 ) 2 The solution was impregnated into CeO by isochoric impregnation method. 2 The surface of the first intermediate with a Pd loading of 6 wt% was obtained, and after drying at 100 °C for 6 h in a vacuum drying oven, the first intermediate was dried in a muffle furnace at a temperature of 100 °C for 6 h. 2 The catalyst was calcined at 400 °C for 3 h in an atmosphere to obtain a single-component supported catalyst.
[0186] The zinc acetate solution was impregnated onto the surface of the above-mentioned single-component supported catalyst by an excessive impregnation method to obtain a second intermediate with a Zn loading of 2 wt%, which was dried at 120° C. for 3 h in a forced air drying oven and then dried in a tubular furnace H 2 The dual-component supported catalyst PdZn / CeO was obtained by calcining at 600 °C for 4 h in an atmosphere. 2 , wherein Pd and Zn exist in alloy form.
[0187] Preparation Example 15
[0188] (1) 80 g of an aluminum source (pseudo-boehmite), 10 g of an acidic compound (10 wt % dilute nitric acid) and 800 mL of water were first mixed in a 1500 mL stirred tank (temperature: 25° C., rotation speed: 600 rpm, time: 1 h) to obtain a first mixture;
[0189] The first mixture was spray-dried (temperature: 100° C., time: 5 h), and then calcined in a muffle furnace at 800° C. for 3 h in static air to obtain microspherical alumina DS-1.
[0190] Among them, the pyridine infrared characterization spectrum of the above-mentioned molded alumina DS-1 is as follows Figure 3 As shown by Figure 3 It can be seen that the molded alumina DS-1 has an extremely high number of B acid sites, and the B acid density is 1.5 μmol / g;
[0191] Among them, the transmission infrared spectrum of the above-mentioned molded alumina DS-1 is as follows Figure 4 As shown in (b), from 4(b), the wave number is 1066cm -1 and 1160cm -1 There are no signal peaks at all places, indicating that there are no Si-O-Si and Si-O-Al bonds in the molded alumina DS-1.
[0192] (2) H 2 PtCl 6 The solution was impregnated onto the surface of the above-mentioned formed alumina DS-1 by an over-impregnation method to obtain a first intermediate with a Pt loading of 5 wt%. After being dried at 100 °C for 5 h in a vacuum drying oven, the first intermediate was dried in a muffle furnace at a temperature of 100 °C for 5 h. 2 The catalyst was calcined at 500 °C for 3 h in an atmosphere to obtain a single-component supported catalyst.
[0193] WillIn(NO 3 ) 3 The solution was impregnated onto the surface of the above-mentioned single-component supported catalyst by saturation impregnation method to obtain a second intermediate with an In loading of 2 wt%. After drying at 80°C for 12 h in a forced air drying oven, the catalyst was dried in a tube furnace H 2 The catalyst was calcined at 600°C for 4 h in an atmosphere to obtain a microspherical two-component supported catalyst PtIn / DS-1, in which Pt and In existed in an alloy state.
[0194] Preparation Example 16
[0195] The method of Preparation Example 1 is followed, except that in step (4),
[0196] H 2 PtCl 6 The solution was impregnated onto the surface of the silicon-modified alumina AS-1 by an over-impregnation method to obtain a first intermediate with a Pt loading of 5 wt%. The first intermediate was dried at 100 °C for 5 h in a vacuum drying oven and then heated to room temperature in a muffle furnace under a static H 2 The catalyst was calcined at 500 °C for 3 h in an aqueous solution to obtain a microspherical single-component supported catalyst Pt / AS-1.
[0197] The XRD spectrum of the active component Pt in the above-mentioned single-component supported catalyst Pt / AS-1 is as follows: Figure 7 As shown by Figure 7 It can be seen that the single-component supported catalyst Pt / AS-1 has the crystal phase peak of Pt nanoparticles, but no alloy crystal phase peak composed of Pt and other non-precious metal components.
[0198] Preparation Example 17
[0199] The method of Preparation Example 1 is followed, except that in step (4),
[0200] H 2 PtCl 6 The solution was impregnated onto the surface of the silicon-modified alumina AS-1 by an over-impregnation method to obtain a first intermediate with a Pt loading of 5 wt%. The first intermediate was dried at 100 °C for 5 h in a vacuum drying oven and then heated to room temperature in a muffle furnace under a static H 2 The catalyst was calcined at 500 °C for 3 h in an atmosphere to obtain a single-component supported catalyst.
[0201] WillIn(NO 3 ) 3 The solution was impregnated onto the surface of the above-mentioned single-component supported catalyst by a saturated impregnation method to obtain a second intermediate with an In loading of 2 wt%. The second intermediate was dried at 80° C. for 12 h in a forced air drying oven and then calcined at 600° C. for 4 h in an air atmosphere in a tubular furnace to obtain a microspherical two-component supported catalyst "PtIn / AS-1", in which Pt and In existed in the form of oxides, respectively.
[0202] Preparation Example 18
[0203] H 2 PtCl 6 The solution was impregnated into TiO 2 The surface of the first intermediate with a Pt loading of 5 wt% was obtained, and after drying at 100 °C for 5 h in a vacuum drying oven, the first intermediate was dried in a muffle furnace at a temperature of 100 °C for 5 h. 2 The single-component supported catalyst Pt / TiO was obtained by calcining at 500 °C for 3 h in an atmosphere. 2 .
[0204] Table 1
[0205]
[0206] Note: 1-Silicon content is expressed as SiO x Count, where 1≤x≤2.
[0207] Table 1
[0208]
[0209] It can be seen from the data in Table 1 that compared with Preparation Examples 9-15 and 18, Preparation Examples 1-8 and 16-17 all use silicon-modified alumina with a specific structure as a carrier, wherein the silicon-aluminum ratio of the silicon-modified alumina is less than 1, silicon is connected to the surface of the alumina through Si-O-Al chemical bonds, and adjacent silicon on the surface of the alumina is connected through Si-O-Si chemical bonds; it also has a lower B acid density, a lower wear index, better crushing strength, better specific surface area and better average pore size.
[0210] Table 2
[0211]
[0212]
[0213] Note: In the 2-component supported catalyst, the first active component and the second active component exist in the form of an alloy.
[0214] It can be seen from the data in Table 2 that, compared with Preparation Examples 16-18, the first active component and the second active component in the two-component supported catalyst prepared by the method provided by the present invention in Preparation Examples 1-15 exist in the form of an alloy, thereby improving the catalytic activity of the two-component supported catalyst.
[0215] Example 1
[0216] In the presence of 50 mL of methanol and 0.4 g of a two-component supported catalyst PtIn / AS-1, 0.2 g of aminocaprolactam was subjected to a methylation reaction in an intermittent autoclave, wherein the conditions for the methylation reaction included: a temperature of 80°C, N 2 The pressure is 0.7 MPa, the time is 4 hours, and a reaction product is obtained, wherein the reaction product includes methylaminocaprolactam, dimethylaminocaprolactam and other by-products;
[0217] The conditions and process parameters of the methylation reaction are listed in Table 3. The catalytic reaction results were analyzed by gas chromatography and the test results are listed in Table 4.
[0218] Specifically, the product was detected by filtering the reaction solution and the catalyst, adding a certain amount of n-decane as an internal standard, mixing the internal standard and the reaction filtrate evenly, and performing gas phase analysis and quantification (Angilent GC7890B; separation column: PONA column (0.32 mm×30 m)).
[0219] The conversion rate of aminocaprolactam = the mass of converted aminocaprolactam / the mass of aminocaprolactam fed × 100%; wherein, the mass of converted aminocaprolactam = the mass of aminocaprolactam – the residual mass of aminocaprolactam.
[0220] Methylaminocaprolactam selectivity=(mass of methylaminocaprolactam÷142) / (mass of converted aminocaprolactam÷128)×100%.
[0221] Dimethylaminocaprolactam selectivity = (mass of dimethylaminocaprolactam ÷ 156) / (mass of converted aminocaprolactam ÷ 128) × 100%;
[0222] Methylated aminocaprolactam selectivity = methylaminocaprolactam selectivity + dimethylaminocaprolactam selectivity.
[0223] Example 2-18
[0224] According to the method of Example 1, the difference is that
[0225] The types of catalysts were replaced with the catalysts prepared in Preparation Examples 2-18, and the conditions and process parameters of the methylation reaction were listed in Table 3. The catalytic reaction results were analyzed by gas chromatography, and the test results are listed in Table 4.
[0226] Comparative Example 1
[0227] According to Chen, J.; Dong, Y.; Xiao, C.; Tao, Y.; Wang, X., Organocatalyzed Ring-Opening Polymerization of Cyclic Lysine Derivative: Sustainable Access to Cationic Poly (ε-lysine) Mimics. Macromolecules 2021, 54(5), 2226-2231; reaction conditions: solvent is formaldehyde, catalyst is 10wt% Pd / C, temperature is 25°C; test results are listed in Table 4.
[0228] Table 3
[0229]
[0230] Table 4
[0231]
[0232]
[0233] Note: 3-methylated aminocaprolactam selectivity = methylaminocaprolactam selectivity + dimethylaminocaprolactam selectivity.
[0234] It can be seen from the data in Tables 3-4 that the preparation method of methylated aminocaprolactam provided by the present invention does not involve alkylating agents such as aldehydes and halogenated hydrocarbons in the reaction, and has a high green reaction path; by adjusting the type of carrier and the content of active components in the catalyst, as well as the dosage ratio of the reactants, it is more conducive to improving the catalytic effect of the catalyst and obtaining highly selective methylated aminocaprolactam (i.e., methylaminocaprolactam and dimethylaminocaprolactam).
[0235] Comparing the data of Examples 1-18, it can be seen that when the dual active components in the catalyst are selected from PtIn, it is more conducive to improving the selectivity of methylated aminocaprolactam.
[0236] Compared with Examples 9-15 and 18, the solution in Example 1-8 using a carrier of silicon-modified alumina with a B acid density of ≤2 μmol / g is more conducive to improving the selectivity of methylated aminocaprolactam.
[0237] Examples 19-22
[0238] According to the method of Example 1, the difference is that
[0239] The conditions and process parameters of the methylation reaction are listed in Table 5. The catalytic reaction results were analyzed by gas chromatography and the test results are listed in Table 6.
[0240] Comparative Example 2
[0241] According to the method of Example 1, the difference is that
[0242] The conditions and process parameters of the methylation reaction are listed in Table 5. The catalytic reaction results were analyzed by gas chromatography and the test results are listed in Table 6.
[0243] Table 5
[0244]
[0245] Table 6
[0246]
[0247] Note: 3-methylated aminocaprolactam selectivity = methylaminocaprolactam selectivity + dimethylaminocaprolactam selectivity.
[0248] It can be seen from the data in Tables 5-6 that the method for preparing methylated aminocaprolactam provided by the present invention effectively improves the selectivity of methylated aminocaprolactam by regulating the conditions (temperature and pressure) of the methylation reaction and the amount of the catalyst within the preferred protection range.
[0249] Compared with Example 1, Example 22 adopts a higher methylation reaction temperature, which is more conducive to improving the selectivity of methylated aminocaprolactam.
[0250] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing methylated aminocaprolactam, characterized in that: In the presence of a catalyst, aminocaprolactam and / or its derivatives are contacted with methanol and subjected to a methylation reaction to obtain methylated aminocaprolactam; Wherein, the methylated aminocaprolactam includes methylaminocaprolactam and / or dimethylaminocaprolactam.
2. The preparation method according to claim 1, wherein The mass ratio of aminocaprolactam and / or its derivatives to the catalyst is 1:0.1-10, preferably 1:0.1-5, more preferably 1:0.5-2; And / or, the aminocaprolactam and / or its derivatives are selected from aminocaprolactam and / or aminocaprolactam salts, preferably at least one selected from DL-α-amino-ε-caprolactam, DL-α-amino-ε-caprolactam hydrochloride, DL-α-amino-ε-caprolactam sulfate and DL-α-amino-ε-caprolactam nitrate.
3. The preparation method according to claim 1 or 2, wherein The usage ratio of the aminocaprolactam and / or its derivatives in g to the methanol in mL is 1:5-1000, preferably 1:20-500, more preferably 1:80-300.
4. The preparation method according to any one of claims 1 to 3, wherein The conditions of the methylation reaction include: temperature of 50-180°C, time of 0.5-24h, and pressure of 0.1-10MPa; Preferably, the conditions of the methylation reaction include: temperature of 60-120° C., time of 1-5 h, and pressure of 0.5-2 MPa.
5. The preparation method according to any one of claims 1 to 4, wherein: The catalyst is a metal supported catalyst, preferably a single-component supported catalyst, a two-component supported catalyst, and more preferably a two-component supported catalyst; Preferably, the two-component supported catalyst comprises a carrier, and a first active component and a second active component supported on the carrier, wherein the first active component and the second active component exist in the form of an alloy.
6. The preparation method according to claim 5, wherein: Based on the total weight of the two-component supported catalyst, the content of the first active component is 0.1-10wt%, preferably 0.2-5wt%; the content of the second active component is 0.1-20wt%, preferably 0.5-10wt%; and / or, the first active component is selected from noble metal elements, preferably selected from at least one of Pd, Pt, Ru, Ir and Rh, more preferably selected from Pd and / or Pt; and / or, the second active component is selected from non-precious metal elements, preferably selected from at least one of Ni, Co, In, Sn, Ga, Zn, Mn and Fe, more preferably selected from at least one of Ni, In, Ga and Zn; And / or, the carrier is selected from oxides and / or modified oxides, the oxide is selected from at least one of Al2O3, SiO2, TiO2, ZrO2 and CeO2, and the modified oxide is selected from silicon-modified alumina.
7. The preparation method according to claim 6, wherein: When the carrier is selected from the silicon-modified alumina, the B acid density of the silicon-modified alumina is ≤2 μmol / g, preferably 0-2 μmol / g, more preferably 0-1.4 μmol / g, and more preferably 0-0.5 μmol / g; And / or, the silicon-modified alumina comprises silicon and alumina, wherein the silicon-to-alumina ratio of the silicon-modified alumina is less than 1, the silicon is connected to the surface of the alumina via Si-O-Al chemical bonds, and adjacent silicon on the surface of the alumina is connected via Si-O-Si chemical bonds; And / or, based on the total weight of the silicon-modified alumina, the content of the alumina is 50-90wt%, preferably 70-80wt%; x The silicon content is 10-50wt%, preferably 20-30wt%, wherein 1≤x≤2; And / or, the specific surface area of the silicon-modified alumina is 100-220m 2 / g, preferably 120-200m 2 / g; average pore size is 10-30nm, preferably 15-25nm; wear index is 1-20%, preferably 1-15%; crushing strength is 50-150N / cm, preferably 70-130N / cm.
8. The preparation method according to claim 6 or 7, wherein: The silicon-modified alumina is prepared by the following method: S1, performing a first mixing of an aluminum source, an acidic compound and water, and sequentially performing molding, a first drying and a first calcination on the obtained first mixture to obtain molded alumina; S2, dissolving the shaped alumina in water, first adding an alkaline compound to adjust the pH to 7-12, and then adding a silicon source for a second mixing to obtain a second mixture; S3, subjecting the second mixture to solid-liquid separation, and subjecting the obtained modified alumina precursor to a second drying and a second calcination in sequence to obtain the silicon-modified alumina.
9. The preparation method according to any one of claims 6 to 8, wherein: The two-component supported catalyst is prepared by the following method: (I-1) loading a first soluble metal salt on the surface of the carrier, and sequentially performing a third drying and a third calcination on the obtained first intermediate to obtain a single-component supported catalyst; (I-2) loading a second soluble metal salt on the surface of the single-component supported catalyst, and sequentially performing a fourth drying and a fourth calcination on the obtained second intermediate to obtain the dual-component supported catalyst; or, (II) loading the first soluble metal salt and the second soluble metal salt on the surface of the carrier, and sequentially subjecting the obtained third intermediate to a fifth drying and a fifth calcination to obtain the dual-component supported catalyst; Wherein, the third calcination, the fourth calcination and the fifth calcination are each independently performed in a hydrogen-containing atmosphere.
10. The preparation method according to claim 9, wherein: The hydrogen content in the hydrogen-containing atmosphere is ≥ 10% by volume, preferably 20-90% by volume; and / or, the loading amount of the first soluble metal salt calculated as the metal element is 0.1-10wt%, preferably 0.2-5wt%; and / or, the loading amount of the second soluble metal salt calculated as the metal element is 0.1-20wt%, preferably 0.5-10wt%; And / or, the conditions of the third calcination, the fourth calcination and the fifth calcination independently include: temperature of 400-800° C., time of 450-750° C., and time of 1-10 h, preferably 1-5 h.
11. Use of the methylated aminocaprolactam prepared by the preparation method according to any one of claims 1 to 10 as a polymerization monomer in the preparation of cleaning / sterilization materials, modified nylon materials, and long-chain branched polymer materials.
12. A cleaning / sterilizing material, characterized in that: The cleaning / sterilization material comprises methylated aminocaprolactam obtained by the preparation method according to any one of claims 1 to 10.
Citation Information
Patent Citations
Alpha-(N-benzyl)amino-epsilon-caprolactam compound as well as preparation method and application thereof
CN103694174A
Alpha-(N-disubstituent) amino-epsilon-caprolactam compound as well as preparation method and application thereof
CN104387323A
Ring opening polymerization method for preparing epsilon-polylysine
CN104629045A
Seven-membered cyclic lysine derivative monomer and preparation method thereof, and antibacterial poly(epsilon-lysine) derivative and preparation method thereof
CN111116472A
Preparation method for anhydrous formaldehyde
CN104447248A
